'Let's Join in': Children and ABC Radio. Issue 1 (2nd January 2020) - Griffen-Foley, Bridget
Abstract : This article considers the world for children created by the Australian Broadcasting Commission (ABC) and its predecessors between the 1920s and the 1970s. Beginning with the 'Aunts' and 'Uncles' of early radio, it looks at the ABC's endeavours in the areas of children's and educational broadcasting, focusing particularly on the Argonauts Club, Kindergarten of the Air and Let's Join In . It also explores the work of ABC identities including composer Bernard Heinze and eurhythmics teacher Heather Gell, and a succession of innovative and committed programmers. But it goes beyond on-air programming to consider the extracurricular world created for young listeners by Australia's public service broadcaster. The article points to the interactivity of Australian broadcasting, examining how a mass medium sought to build communities of young listeners across Australia, and the role of ABC programmes and associated activities in children's lives.